2019
DOI: 10.11604/pamj.supp.2019.33.2.17608
|View full text |Cite
|
Sign up to set email alerts
|

Integrated disease surveillance and response implementation in Liberia, findings from a data quality audit, 2017

Abstract: Introduction in spite of the efforts and resources committed by the division of infectious disease and epidemiology (DIDE) of the national public health institute of Liberia (NPHIL)/Ministry of health to strengthening integrated disease surveillance and response (IDSR) across the country, quality data management system remains a challenge to the Liberia NPHIL/MoH (Ministry of health), with incomplete and inconsistent data constantly being reported at different levels of the surveillance system. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 7 publications
1
31
0
Order By: Relevance
“…The quality of data management system remains a challenge, with incomplete and inconsistent data constantly being reported at different levels of the surveillance system. In Ethiopia, Liberia and Tanzania, assessments of the information systems have identi ed some data quality issues and lack of use of the generated data [45,56,72,83,84]. In a study in Ethiopia, though the surveillance system was found to be simple, useful, exible, acceptable and representative, it lacked regular data analysis and feedback dissemination [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of data management system remains a challenge, with incomplete and inconsistent data constantly being reported at different levels of the surveillance system. In Ethiopia, Liberia and Tanzania, assessments of the information systems have identi ed some data quality issues and lack of use of the generated data [45,56,72,83,84]. In a study in Ethiopia, though the surveillance system was found to be simple, useful, exible, acceptable and representative, it lacked regular data analysis and feedback dissemination [35].…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of a few countries (Burkina Faso, Ghana, Liberia, Uganda) that analyse and use routine HMIS data at sub-national levels in Africa [29,45]. In terms of data utilisation, in both Tanzania [56] and Liberia [45], it was found that analysis and data-use have not been given adequate attention. Underutilization of IDSR data at all levels of the health system was reported as a result of poor data management and analysis skills.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of data management system remains a challenge, with incomplete and inconsistent data constantly being reported at different levels of the surveillance system. In Ethiopia, Liberia and Tanzania, assessments of the information systems have identi ed some data quality issues and lack of use of the generated data [45,56,72,83,84]. In a study in Ethiopia, though the surveillance system was found to be simple, useful, exible, acceptable and representative, it lacked regular data analysis and feedback dissemination [35].…”
Section: Discussionmentioning
confidence: 99%
“…A government health facility, the Tellowayan Memorial Hospital (TMH) alone reported DBVs to the MoHSW in 2008-2013. However, by 2017 some 20 other clinics/hospitals reported DBVs to the LNIH, in addition to TMH [14]. https://doi.org/10.1371/journal.pntd.0008957.g001…”
Section: Study Areasmentioning
confidence: 99%
“…Deterministic model for forecasting 2014-2016 missed DBV data. Due to the prevailing challenges of EVD epidemic in West African that resulted in severe humanitarian crisis of international concern [14,18], no human hospital records of dog bite victims in 2014-2016 were available to the authors at the county reference hospitals and at the Liberian NIH. Thus, we utilized predicted case of DBVs from deterministic model of projected data for 2014-2017 expected for Buchanan, Gbarnga and Voinjama.…”
Section: Data Sourcesmentioning
confidence: 99%